2020
DOI: 10.3390/d12120469
|View full text |Cite
|
Sign up to set email alerts
|

Current State and Drivers of Arable Plant Diversity in Conventionally Managed Farmland in Northwest Germany

Abstract: Agricultural intensification has led to dramatic diversity losses and impoverishment of the arable vegetation in much of Europe. We analyzed the status of farmland phytodiversity and its determinants in 2016 in northwest Germany by surveying 200 conventionally managed fields cultivated with seven crops. The study was combined with an analysis of edaphic (soil yield potential), agronomic (crop cover, fertilizer and herbicide use) and landscape factors (adjacent habitats). In total, we recorded 150 non-crop plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…This suggests that there was an obvious difference between the weed composition of field edges and field cores. This result seems to be in line with observations previously reported from soybean and oil pumpkin fields in Hungary (Pinke et al., 2016, 2018) and other recent European studies (Wietzke et al., 2020; Yvoz et al., 2021). The influence of plot location on weed distributions can have many explanations.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This suggests that there was an obvious difference between the weed composition of field edges and field cores. This result seems to be in line with observations previously reported from soybean and oil pumpkin fields in Hungary (Pinke et al., 2016, 2018) and other recent European studies (Wietzke et al., 2020; Yvoz et al., 2021). The influence of plot location on weed distributions can have many explanations.…”
Section: Discussionsupporting
confidence: 93%
“…A similar pattern in oilseed rape in France also was confirmed by Berquer et al (2021), who reported that weed assemblages in field cores are mainly shaped by crop height (indicating crop competition), while height has little effect in the field margins. Additionally, the effects of intensive crop management generally decrease towards the field periphery (Pinke et al, 2012;Wietzke et al, 2020;Yvoz et al, 2021), and the differences between field edge and field core can also be less marked when crop management intensity is lower (Yvoz et al, 2021).…”
Section: Environmental Variables and Plot Locationmentioning
confidence: 99%
“…For example, S. annua, a retreating melliferous weed with great ecological and historical value [88], sometimes thrived in large quantities in such fields. In contrast, the spayed phacelia crops usually hosted only a few common weed species, such as the majority of conventional farmlands in Europe, where agricultural intensification absolutely impoverished the arable weed flora [89]. This highlights the importance of extensification in phacelia crops for the conservation of rare arable plants in Europe [90].…”
Section: Biodiversity Issuesmentioning
confidence: 99%
“…Basically, the plant communities of the surveyed SRC and all other investigated habitat types were dominated by widespread, common and non-threatened plant species. In our study region, the presence of species of conservation concern was not expected, since the establishment potential for these species is limited due to many decades of intensive agricultural use [66][67][68]. However, in many other studies on SRC in different regions of Germany and in other European countries [22][23][24][25][26]29,33,54,55,69], these woody crops did not prove to be a habitat of major importance for rare or threatened plant species.…”
Section: Discussionmentioning
confidence: 78%